2004
DOI: 10.1002/chem.200305506
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure, Spectroscopy and Matrix Photochemistry of Fluorocarbonyl Iodide, FC(O)I

Abstract: The molecular structure of FC(O)I has been determined by gas electron diffraction. High-level ab initio methods, including coupled-cluster and the new correlation-consistent basis sets for fourth row elements, have been used to calculate the structure of FC(O)I. A comprehensive vibrational spectroscopic study (both IR and Raman) complemented by high-level calculations has also been performed. Furthermore, UV, mass, and NMR spectra have been recorded for FC(O)I. The matrix photochemistry of FC(O)I has been stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…As previously reported for complexes between CO and halogen or interhalogen molecules, different linear structures are plausible for the complexes, arising from the donor possibilities of either the C or the O atoms of the CO molecule. In the present case, the experimental blue-shift wavenumber of the CO vibration is consistent with the predictions for the OC···F 2 structure.…”
Section: Resultssupporting
confidence: 59%
“…As previously reported for complexes between CO and halogen or interhalogen molecules, different linear structures are plausible for the complexes, arising from the donor possibilities of either the C or the O atoms of the CO molecule. In the present case, the experimental blue-shift wavenumber of the CO vibration is consistent with the predictions for the OC···F 2 structure.…”
Section: Resultssupporting
confidence: 59%
“…As an extension of our previous study on the interaction of CO with IF in Ar matrix, 2 we report in this contribution on the molecular complexes of the remaining halogen fluorides ͑ClF and BrF͒. As an extension of our previous study on the interaction of CO with IF in Ar matrix, 2 we report in this contribution on the molecular complexes of the remaining halogen fluorides ͑ClF and BrF͒.…”
Section: Introductionmentioning
confidence: 56%
“…There is only one experimental study dealing with the interaction of ClF and CO. 3 Hinds et al 3 analyzed the rotational spectra of several isotopomers of the OC¯ClF complex. 2 To generate the CO/ClF and CO/BrF complexes in a similar way as shown for CO/IF, 2 the precursors FC͑O͒Cl and FC͑O͒Br ͑Refs. It has been shown that this interaction is stronger than a van der Waals or dipole-dipole attraction and charge redistribution takes place between both CO and XY.…”
Section: Introductionmentioning
confidence: 99%
“…This allowed us to follow the course of the reaction and to observe the purification process. The starting materials FC(O)OOC(O)F, FC(O)I, and FC(O)OCF 3 were prepared according to literature procedures and stored in flame-sealed glass ampules under liquid nitrogen in a long-term Dewar vessel. The ampules were opened with an ampule key on the vacuum line, appropriate amounts were removed for the experiments, and then the ampules were flame-sealed again.…”
Section: Methodsmentioning
confidence: 99%